FAKTOR FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK BERKARIR SEBAGAI AKUNTAN PUBLIK (Studi Kasus pada Perguruan Tinggi dengan Program Studi Akuntansi yang Berakreditasi B yang terdapat di Pekanbaru) - Annisa Rindani; Kennedy -; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of; intrinsic factors of work, financial rewards, labor market consideration, work social values, professional training, and professional rewards in choosing career as public accountant. It is expected that this research can help the students in considering the career they will choose. The sample of this research is the accounting students in University of Riau (UR), State Islamic University (UIN), and Islamic University of Riau (UIR) in Pekanbaru. The data is collected by using questionnaire survey. From 100 questionnaires given, 100 questionnaires are given back to the researcher, and the totals of questionnaire that can be analyzed are 92 questionnaires. The data collected is analyzed by multiple regression by using SPSS version 17.0. The result of this research showed that intrinsic factors of work, financial rewards, consideration of labor market and professional training has influence in career choosing as public accountant. Whereas, work social values and professional rewards do not has influence in career choosing as public accountant.Keywords: accounting students, career choosing, and public accountant.